Effect of Job Satisfaction of Elementary School Teachers on School Effectiveness (Journal of Social Sciences Review, 2023)
This study examines the impact of job satisfaction on school effectiveness among elementary school teachers using a convenient sampling technique with a sample size of 100 teachers. The purpose of this research is to determine the relationship between job satisfaction and school effectiveness, and how the former can influence the latter. The study used a mixed-methods approach to collect data, including both quantitative and qualitative methods. The quantitative data were collected through a questionnaire survey, while the qualitative data were gathered through semi-structured interviews. The findings of this study reveal a significant positive relationship between job satisfaction and school effectiveness among elementary school teachers. The results also show that job satisfaction influences the commitment, motivation, and engagement of teachers in their work, leading to improved student outcomes and school performance. The study concludes that enhancing the job satisfaction of elementary school teachers can contribute to improving school effectiveness and enhancing the quality of education.
Keywords: Job Satisfaction, Elementary School, Effectiveness